A INFLUÊNCIA DE FATORES HISTÓRICOS NA DIVERSIFICAÇÃO DE POPULAÇÕES DE Pitcairnia azouryi (BROMELIACEAE) RESTRITA A INSELBERGS DA FLORESTA ATLÂNTICA - Sheu, Yumi (2020)
Phylogeography investigates the evolutionary processes that govern the distribution of species on a spatial and temporal scale. Countless studies use phylogeographic approaches to understand the diversification of species in the context of regions with hi